Analisis Makna Kasih Sayang Orang Tua dalam Lukisan “Ibu Dan Anak” Karya Basuki Abdullah - Talitha, Talitha Anindya; Budi, Setyo (Program Studi Pendidikan Seni Rupa FBS UNJ, 2025)
Painting is often a medium to express deep meaning including emotional feelings. Basuki Abdullah is an Indonesian painting maestro who is known for his realist style and often presents human portraits with emotional expressions. One of his works, the painting “Mother and Child” created in 1992, features a mother holding her child which gives an emotional impression such as the feelings of love and struggle of a mother towards her child to provide protection and great sacrifice to the child. So this work seems to be a general embodiment of a mother's boundless love. This research aims to identify and analyze the meaning of parental love expressed in the painting “Mother and Child” by Basuki Abdullah, as well as explore the visual elements and aesthetic responses generated from the painting. The approach method used is qualitative-descriptive by collecting data through observation, literature study, and visual analysis as data collection techniques. The results show that through the use of color, gesture, and composition, Basuki Abdullah presents a deep emotional message, making this work a symbol of eternal love between parents and children.